Injury prevention relevance: markerless functional performance testing in athletes with chronic ankle instability to inform recurrent sprain risk screening - Seyhan, Sinan; Acar, Gorkem; Bilici, Muhammed Fatih; Girginer, Fatma Gozlukaya; Bilici, Omer Faruk; Soylu, Caglar (Bmc, 2026)
Objective To compare functional performance between athletes with chronic ankle instability (CAI) and healthy controls using objective motion analysis, and to determine whether CAI-related deficits are more evident in agility and multidirectional hop tasks than in general vertical jump measures. Methods Thirty-two athletes participated in this cross-sectional study, including 16 athletes with CAI and 16 healthy controls. Functional performance was assessed using the DeepSport motion analysis system and included countermovement jump (CMJ), agility tests (5-10-5 and acceleration-deceleration-acceleration [ADA]), and multidirectional hop tasks. Subjective instability and injury history were evaluated using the Cumberland Ankle Instability Tool (CAIT) and clinical history variables. Between-group comparisons were performed using analysis of covariance adjusted for sex. Additional group & times; sex interaction and male-only sensitivity analyses were conducted to examine the potential effect of sex imbalance. An exploratory regression analysis within the CAI group examined the association between previous ankle sprain history and triple crossover hop performance. Results No significant between-group differences were observed for age, height, body mass, or body mass index (all p > 0.05), whereas CAIT score and injury-history variables differed significantly between groups (all p < 0.001). After adjustment for sex, CMJ height, CMJ power, and CMJ flight time did not differ significantly between groups. In contrast, athletes with CAI showed significantly poorer performance in the 5-10-5 agility test (F(1,29) = 14.62, p = 0.001), side jump test (F(1,29) = 35.80, p < 0.001), 6-m jump test (F(1,29) = 6.58, p = 0.016), single-leg hop test (F(1,29) = 5.12, p = 0.031), triple crossover hop distance (F(1,29) = 19.22, p < 0.001), and lateral hop distance (F(1,29) = 30.07, p < 0.001). ADA outcomes were numerically poorer in the CAI group but did not reach statistical significance after sex adjustment. Within the CAI group, a greater number of previous ankle sprains was associated with shorter triple crossover hop distance; however, because the overall regression model was not statistically significant (R & sup2; = 0.31, p = 0.087), this finding was considered exploratory and hypothesis-generating only. No significant group & times; sex interaction was detected for any primary outcome, and male-only sensitivity analyses showed a consistent pattern for the main agility and hopping variables. Conclusion Athletes with CAI demonstrated meaningful deficits in agility and multidirectional hop performance, whereas general vertical jump variables were less discriminative after sex adjustment. These findings suggest that multidirectional hop and agility tests may be more sensitive than CMJ-derived outcomes for identifying functional limitations in athletes with CAI. The exploratory association between sprain history and triple crossover hop performance requires confirmation in larger, adequately powered studies. Overall, the results support the inclusion of multiplanar hop and agility assessments in the functional evaluation and rehabilitation monitoring of athletes with CAI.
Keywords: Chronic Ankle Instability; Physical Functional Performance; Performance Tests; Ai Motion Analysis; Countermovement Jump (Cmj)